THE INFLUENCE OF REFERENCE GROUPS AND SOCIOECONOMIC STATUS OF PARENTS OF HIGH SCHOOL STUDENTS OF SUNAN GIRI CITY PROBOLINGGO ON COLLEGE SELECTION INTENTIONS - Yahya Ulumuddin; Didit Darmawan (Journal of Innovation Research and Knowledge, 2024)
College has an important role in shaping the future of students, and the decision to choose a college is a crucial step in their educational journey. For this reason, this study aims to determine the effect of reference groups and parents' socioeconomic status on college selection intentions among Sunan Giri High School students in Probolinggo City. This study used a quantitative approach with a population of 46 XII grade students at Sunan Giri High School, Probolinggo City. The method that can be used to evaluate the effect of these variables on college selection intentions is multiple linear regression analysis. In this study, the results show that there is a significant influence between reference groups and parents' socioeconomic status on the college selection intentions of Sunan Giri High School students in Probolinggo City. The results of this study confirm the important role of reference groups in shaping students' intention to choose a college. Peers and the social environment around students have a significant impact in shaping college-related perceptions and preferences. Parents' socioeconomic status was also shown to play an important role. Students who come from a more stable economic background tend to have a higher intention to choose a college